PENGARUH COST OF BORROWING, PROFITABILITY DAN COLLATERAL VALUE OF ASSETS TERHADAP STRUKTUR MODAL PADA PERUSAHAAN REAL ESTATE DI INDONESIA - Ade Suryana (Majalah Ilmiah Bijak, 2016)
Genarlli, the main goal of a company is to maximize its shareholders’ wealth. For a public company, it means maximizing return to its outstanding shares. The final decisions made by the management, which comprise of investment decision and financing decision. Real estate industry is a capital-intensive industry that would spend large fund to start the operations. Consequently, most real estate companies would search and rely upon loan from third parties as its main financing source other than its own capital.The objective of this research is to reveal whether there is influence of cost of borrowing, profitability, and collateral value of assets on capital structure.Th hypothesis for this research are: (a) to reveal whether there is influence of cost of borrowing on capital structure in real estate companies in Indonesia, (b) to reveal whether there is influence of profitability on capital structure in real estate companies in Indonesia, (c) to reveal whether there is influence of collateral value of assets on capital structure in real estate companies in Indonesia, and (d) to reveal whether there is influence of cost of borrowing, profitability and collateral value of assets, simultaneously, on capital structure in real estate companies in Indonesia.Using multiple linear regressions to test those hypotheses, the data obtained from real estate companies listed in Indonesia Stock Exchange during 2003-2007 revealed that: (a) there is negative and significant influence of cost of borrowing on capital structure in real estate companies in Indonesia, (b) there is positive and significant influence of profitability on capital structure in real estate companies in Indonesia, (c) there is positive and significant influence of collateral value of assets on capital structure in real estate companies in Indonesia, and (d) there is  significant influence of cost of borrowing, profitability and collateral value of assets, simultaneously, on capital structure in real estate companies in Indonesia.The result of this research indicated that cost of borrowing is the factor that significantly determines the capital structure. Obtaining loan from third parties would result higher interest expenses, and in turn result in low net income, compared to companies that use their own source of financing. Of course, the decision to finance a company through loan facilities should be based on in-depth analysis and calculation especially in relation to the company’s capability for settlement.